PRIMARY IMMUNODEFICIENCIES WITH ECZEMATOUS MANIFESTATION : AN UPDATED REVIEW - Ribarski, Ordanche; Damevska, Katerina (Journal of Morphological Sciences, 2024)
Mutations in the set of genes responsible for adequate development and function of the immune system also affect the s kin-associated lymphoid tissue (SALT) . As a result of inborn genetic errors, patients develop one of the 430 different primary immunodeficiencies defined to date. Globally, nearly 6 million people are living with a primary immunodeficiency, with an estimated incidence of 1 case per 10.000 inhabitants. Despite modern and accessible diagnostic technologies, patients still receive delayed diagnoses. We conducted a search for original articles, review articles, and case reports published in scientific journals available in the PubMed database by using the following keywords: primary immunodeficiency AND eczematous rash OR skin manifestations. This review article mainly focuses on skin manifestations of primary immunodeficiencies with eczematous rash. Keywords: primary immunodeficiency, eczematous lesions, skin manifestations, Wiskott-Aldrich Syndrome, Autosomal dominant hyper-IgE syndrome, Autosomal recessive hyper-IgE syndrome, Comèl-Netherton syndrome, Omenn syndrome, IPEX syndrome.